The Case for Depositor Preference. (Technical Notes and Manuals; Technical Notes and Manuals ;, 2020)
This technical note and manual (TNM) addresses the following issues: advantages and disadvantages of different types of depositor preference, international best practice and experience in adopting depositor preference, and introducing depositor preference in jurisdictions with or without deposit insurance.